Medication Adherence by Pill Count Method and Changes in Mean Arterial Pressure Among Community Members with Hypertension: A Pre-Experimental Study - Ikhsanuddin; Elnika Saragih; Nur Asnah Sitohang; Mula Tarigan; Lilis Nuriyanti Tambun (Talenta Publisher, 2026)
Poor medication adherence contributes to inadequate blood pressure control and increases the risk of hypertension-related complications. The pill count method using a pill box is a simple, objective, and low-cost strategy for monitoring medication adherence in community settings. Therefore, this study aimed to evaluate medication adherence using the pill count method and explore the association with short-term changes in mean arterial pressure (MAP). A pre-experimental one-group pretest–posttest study was conducted among 33 hypertensive patients. Medication adherence was monitored for seven consecutive days using a pill box. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and MAP were measured before and after the observation period, then collected data were analyzed with the Wilcoxon Signed-Rank test. A total of 28 participants (84.8%) showed high medication adherence, with a median adherence of 100% (IQR: 86–100). Significant reductions were observed in SBP (median change: −3.0 mmHg, p = 0.014), DBP (−3.0 mmHg, p = 0.006), and MAP (−3.3 mmHg, p = 0.006). However, these reductions were modest over the seven-day observation period. High medication adherence was followed by modest short-term reductions in blood pressure parameters. These findings should be regarded as exploratory rather than confirmatory and should not be interpreted as evidence of a causal relationship because of the pre-experimental design. Nevertheless, the pill count method appears to be a practical, objective, and low-cost approach for monitoring medication adherence in community-based hypertension management. Keyword: Hypertension, Medication Adherence, Pill Count Method, Mean Arterial Pressure